When the project ends: institutional ownership and the long-term sustainability of university–community partnerships in Indonesia - Abu Tholib (Indonesian Journal of Applied Community Research, 2026)
Background: Post-project sustainability remains a persistent problem in university–community partnerships, especially in post-disaster settings such as Candipuro, Lumajang, where BNPB recorded 10,395 displaced persons across 410 evacuation points after the Semeru eruption. Objective: This community engagement program aimed to strengthen institutional ownership among 40 eligible local actors from village institutions, relocation representatives, volunteers, schools, women’s groups, youth representatives, and livelihood groups in Sumbermujur and Sumberwuluh. Method: The method integrated planning, implementation, and monitoring-evaluation through needs assessment, pre-post questionnaires, observation checklists, product rubrics, FGD guides, attendance records, and partner validation forms. Results: During planning, this program conducted three coordination meetings, recorded 42 needs assessment responses, mapped six stakeholder groups, and prepared five evaluation instruments. During implementation, this program delivered one orientation, three core training sessions, eight weeks of mentoring, two peer discussion forums, and recorded 70% practice-output completion. Implication: During monitoring-evaluation, this program recorded 82% attendance, 70% acceptable outputs, a 20-point pre-post capacity score increase, two validation forums, one institutional follow-up plan, and a 3–6 month monitoring agreement. Novelty: The novelty of this program lies in integrating data-based planning, practice-oriented mentoring, participatory validation, and institutional follow-up as a measurable model for sustaining university–community partnerships after project completion.